Pengembangan Bahan Ajar Matematik Berbasis Inkuiri Berbantuan Multi Media Untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMA Se-Provinsi Sumatera Utara - Rajagukguk, Waminton; Fauzi, KMS. Muhammad Amin; Hia, Yasifati (Jurnal Pendidikan Matematika dan Sains, 2017)
This study aims to develop inquiry based multimedia mathematics teaching materials that can improve the critical thinking skills of high school students in North Sumatera. This research was conducted in North Sumatera Province, from 2016 to 2018. The population of this research is all SMA in North Sumatera Province. The subject of this research is high school students. The sampling technique used purposive random sampling, which is choosing six SMA randomly with three SMA Negeri and three private SMA. To know the influence of mathematics materials based on inquiry of multi media aid developed used quasi experimental research design with control group post test only design. Data collection techniques used questionnaires, observations, and tests. Data were analyzed using descriptive analysis technique, t test and anava. Tests of research found inquiry learning model in groups make students dare to express opinions and accept opinions of others. Multilingual aided instructional learning model interacts with students early mathematical abilities of critical thinking skills. Initial students with moderate and higher category skills prefer to use multimedia-based inquiry learning models, whereas for early low-ability students it is better to use ordinary or expository learning models. Critical thinking ability of students more in the medium category that is equal to 38.71%, this means to improve critical thinking skills in this study need to note one of the 3rd limitation in giving more opportunities for students to think creatively.